Can quality of work life affect work performance among Government Agriculture Extension Officers? a case from Malaysia - Mohamed Shaffril, Hayrol Azril; Uli, Jegak; Asiah, M.; Ali , Noor Azman; Abu Samah, Bahaman; Othman, Jamilah; Thomas, K. (Science Publications, 2010)
The importance of agriculture industry in enhancing the country economy cannot be denied. Recently, a total of USD 1.7 billion has been allocated by the government to boost this industry. Beside of this huge allocation, do the policy implementers which are the agriculture extension officers have adequate work performance to carry out the responsibility given to them? Approach: This study would like to discover whether quality of work life among the agriculture extension employee do have impact their work performance or not. It is necessary to estimate quality of work life function in enhancing work performance, analyze the most important factor and variables on this work performance. The instruments used for collecting data were: A scale on individual and family life, a scale on safety and security on the organization, a scale on interpersonal relationship in the organization, a scale on job satisfaction, a scale on organizational policies and management style, a scale on personnel health and well being, a scale on work environment, a scale on remuneration and a scale on organizational support. The data were analyzed PASW software. Results: Results depict that all of the nine qualities of work life studied have significant and positive relationship with work performance where the highest relationship occurred between individual and family life with work performance. Multiple regression analysis demonstrated that five factors which are individual and family life, job satisfaction, organization policy and management style, work environment and remuneration are the main contributors to work performance among government agricultural extension employees. Conclusion / Recommendations: From the results gained, it can be concluded that aspect of individual and family life is the highest contributor to work performance among government agriculture extension officer. It can be noted that more courses on how to manage individual and family life should be intensified. A specific counseling department should be established within agriculture agencies in Malaysia. From this study, it is recommended for the future researchers to investigate more on the influence of individual and family life on work performance and work satisfaction in Malaysia.